2019
DOI: 10.1111/eip.12926
|View full text |Cite
|
Sign up to set email alerts
|

Screening for the at‐risk mental state in educational settings: A systematic review

Abstract: Aim: The at-risk mental state (ARMS) allows clinicians to identify individuals who have an increased risk of developing psychosis. At present, most screening for psychosis-risk is carried out within help-seeking populations; however, screening within educational settings may allow clinicians to identify individuals at-risk earlier and to increase the rate of detection. This review aimed to examine screening for the ARMS in educational settings, with the key questions: what screening tools have been used in edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
(113 reference statements)
0
17
1
Order By: Relevance
“…The prevalence of ARMS + adolescents in our sample (26%) was higher than previously reported [6,29]. It can be attributed to the sampling bias, subjects with subtle symptoms are more prone to participate in testing.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The prevalence of ARMS + adolescents in our sample (26%) was higher than previously reported [6,29]. It can be attributed to the sampling bias, subjects with subtle symptoms are more prone to participate in testing.…”
Section: Discussioncontrasting
confidence: 69%
“…Since the ARMS was developed for a population of help-seeking individuals, the data on prevalence of the ARMS status in general population are rather scarce [5]. A recent systematic review of nine studies with non-help seeking individuals indicated ARMS prevalence of 1 to 8%, depending on the questionnaire used [6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last years, the focus of psychosis research has increasingly shifted to non-clinical populations [ 24 ], as authors have argued that systematic and standardized screening for PE could be feasible in community and educational settings [ 25 27 ]. One of the most frequently used screening tools is the Community Assessment of Psychic Experiences (CAPE) [ 28 ], which was created following the theoretical framework of the extended subclinical psychosis phenotype [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loewy et al, 2011) has also been developed. The authors have chosen to use the PQ‐16 in this population as it balanced the greatest sensitivity and specificity and positive predictive values in previous non‐help‐seeking populations (Howie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%